Al código del trabajo debe incorporarse disposiciones para que el empleador provea del transporte, alimentación, medios de seguridad, servicios médicos, a los trabajadores que laboran en el sector rural - Pachar Ordoñez, Edwin Efraín (2014)
he rural workers who are mostly farmers, who through their agricultural labor to make the land produce and supply local and inter mercados, which are usually employed to which they do not provide the means necessary that the Labour Code protects them another very important sector workers; these workers are very important as well as others whose employers do not join the Ecuadorian Institute of Social Security, do not have transportation to commute to work, they have to provide it food workers themselves lack the physical security means, do not have a health center in the unlikely event of a disease, in order are alien to all social services to which you are entitled in an employed or is under dependency. It is important that your employees work to strengthen sustainable development they do, because agricultural and rural workers are an essential factor in facilitating the achievement of sustainable development in view of its relation to industrial change, the high priority they give to the protection of the working environment and the natural environment that surrounds it. Waged agricultural workers is a significant segment of the rural labor force, it must be recognized workers for its key role for both sustainable agriculture and rural development, such as for industrial change and environmental protection. Despite the large number of women and men working as employees in agriculture and are at the heart of the food production system for the trade itself, have been ignored to date, these wage laborers are the agricultural labor force in Ecuador and they and their families are provided the rural poor in many provinces, waged agricultural workers not own or rent the land on which they work, or the tools and equipment they use, in this respect, are different from the farmers group, however, these workers remain invisible when speaking of goals, policies, programs and activities to eliminate poverty and strengthen the role of groups in civil society in the promotion of agriculture and rural development sustainable national food security and sustainable development in each province. A challenge of these summits is to ensure the full recognition of rural agricultural wage workers as a distinct professional group and as workers who can contribute greatly to sustainable agriculture and sustainable development and food security in terms of knowledge, skills and experience and as a social group should be empowered to fight poverty in which many of them; the right of agricultural workers and small farmers to adequate food and sustainable livelihoods can only be achieved as part of a broader political and social rights guarantee, sustainable agriculture and rural development are an integral and necessary components of sustainable development based on the economic, social and environmental development, the importance they represent in the economy is necessary to take them out of the closet and are granted all rights as all workers.